Teachers’ preparedness for the utilization of artificial intelligence in classroom assessment: the contributory effects of attitude toward technology, technological readiness, and pedagogical beliefs with perceived ease of use and perceived usefulness as mediators - Ofem, Usani Joseph; Orim, Faith Sylvester; Edam-Agbor, Imelda Barong; Amanso, Eme Orok Iban; Eni, Eni; Ukatu, James Omaji; Ovat, Sylvia Victor; Osang, Anastecia William; Dien, Constance; Abuo, Cyril Bisong (Frontiers in Education, 2025)
The adoption of Artificial Intelligence (AI) in classroom assessment is widely acknowledged as a game-changer for improving educational outcomes. Despite this, there is a limited body of research addressing the readiness of teachers to implement these technologies. This study bridges that gap by investigating how attitude toward technology, technological readiness, and pedagogical beliefs contribute to teachers’ preparedness, with perceived ease of use and perceived usefulness serving as mediating factors. Data were gathered through a cross-sectional survey involving 3,781 respondents from various institutions. Rigorous quantitative validation confirmed the reliability of the findings. The results indicate that both perceived ease of use and perceived usefulness significantly influence teachers’ willingness to adopt Artificial intelligence, with pedagogical beliefs and technological readiness being particularly influential. Notably, attitude toward technology was found to have a direct impact on perceived ease of use, while pedagogical beliefs and technological readiness affected both perceived ease of use and perceived usefulness. Furthermore, perceived ease of use acted as a mediator between attitude toward technology and preparedness, while perceived usefulness mediated the link between technological readiness and preparedness. The study concludes with a discussion of the findings’ implications and provides actionable recommendations for fostering AI adoption in classroom assessment practices.